X-ray absorption spectroscopy analysis and magnetic properties of M-doped TiO2 nanoparticles (M=Co, Mn, Ni and Zn) prepared by co-precipitation method - Wattanawikkam, Chakkaphan; Pecharapa, Wisanu; Ishihara, Keiichi N. (My University, 2017)
M-doped TiO2 nanoparticles (M=Co, Mn, Ni and Zn) were synthesized by co-precipitation method combined with annealing at 500 °C for 2 h. X-ray diffraction (XRD) was used to identify their structural phases. X-ray absorption near edge structure (XANES) was conducted to probe the chemical state and crystal atomic structure of prepared samples. Magnetic properties of all samples were characterized by vibrating sample magnetrometer (VSM). The XRD analyses reveal that all samples crystallize in anatase tetragonal structure with no additional peaks. The XANES spectra exhibit triple pre-edge fingerprint of Ti4+ of oxidation state with six-fold octahedral coordinate structure. Co-, Ni- and Zn- K-edge results indicate that the Co, Ni and Zn ions in M-doped TiO2 are in 2+ formal oxidation state. Meanwhile, Mn-doped TiO2 sample contains the different oxidation states of 3+ and 4+. The amount of each oxidation state is confirmed by using linear combination fitting method. The magnetic measurement illustrates the paramagnetic behavior for Co-, Mn- and Ni- doped samples that strongly depend on the doping content and no hysteresis loop is observed in undoped and Zn-doped samples.
Keywords: Magnetic properties; TiO2; Transition ions doped; XANES